SPECTRUM OF COMPLICATED DENGUE FEVER IN RAWAL INSTITUTE OF HEALTH SCIENCES ISLAMABAD: A CROSS SECTIONAL STUDY - Ahmed, Khwaja Ashfaq; Nadia Shams; Naseer, Muhammad Asif; Hamayun Manzoor Ahmad (Journal of University Medical & Dental College, 2020)
ABSTRACT BACKGROUND & OBJECTIVE: Pakistan has been facing frequent dengue fever epidemics for the last decade. The current study aims at various complications of dengue fever and their association with age, gender, serology, duration, and symptoms. METHODOLOGY: This cross-sectional study was conducted at the Medicine department, RIHS Islamabad, over eight months of duration after ethical approval. The dult indoor dengue fever cases were selected by consecutive sampling and informed consent obtained. Cases with malaria co-infection, hematological disease, and severe systemic illness were excluded. The symptoms, hematological counts, serology (dengue NS-1, IgG, and IgM), liver function tests, coagulation profile, pneumonia, and pericardial effusion, were documented. Data were analyzed by SPSS V-22. RESULTS: Among 75 cases, 19(25%) were females and 56(75%) males. The mean age was 33.5+12.7. The mean duration of symptoms was 5.4+2.0 days. Dengue NS-1 was positive in 45(60%), IgM in 22(29%), and IgG in 8(11%). Symptoms observed were fever 97%, headache 53%, pain abdomen 35%, vomiting 48%, rash 17%, and body aches 39%. Complicated Dengue fever was seen in 21(28%). Complications include gum bleed 12%, liver impairment 6.6%, gastrointestinal bleed 5%, per-vaginal bleed 4%, epistaxis 4%, hematuria 3%; pleural effusion, ascites and pneumonia 2.6% each, pericardial effusion 1.3% and one expiry. Age, gender, dengue serology, and hematological profile wasn’t found to be associated with complications. CONCLUSION: Complications are frequent in indoor dengue cases that include hemorrhagic complications, liver impairment, effusions, and pneumonia. Early presentation to the hospital may be helpful to screen for impending complications with improved morbidity and better patient care.